IN-VITRO ANTIOXIDANT, LIPID PEROXIDATION INHIBITION AND LIPID PROFILE MODULATORY ACTIVITIES OF HB CLEANSER®BITTERS IN WISTAR RATS - Aderonke, SHORINWA Olusayo; Chinonso, BENNETH Victoria (Universal Journal of Pharmaceutical Research, 2022)
Background: HB cleanser® bitters is a polyherbal formulation with six medicinal plants as phytoconstituents which is being sold to the public for the treatment of various diseases. Hence, it becomes pertinent to evaluate the likelihood of health issues that may be associated with its consumption to provide information to the public on the biological activity and safety. Objectives: This study was conducted to investigate the in vitro antioxidant, lipid peroxidation inhibition and lipid profile effects of HB cleanser® bitters in Wistar rats. Methods: In vitro antioxidant activity was carried using 2,2-diphenyl-1-picryl-hydrazyl (DPPH) assay, nitric oxide scavenging activity, ferric reducing antioxidant power assay. Inhibitory activity on lipid peroxidation was also measured. Phytochemical evaluation was done. Twenty-eight male rats were allotted into four groups of seven animals each. Group A received 5 ml/kg normal saline while groups B, C and D were administered with 1 ml/kg, 1.03 ml/kg and 1.29 ml/kg of the bitters based on the manufacturer’s recommendation through the oral route for 28days consecutively. Lipid parameters assayed were total cholesterol, total triglyceride, high density lipoprotein-cholesterol (HDL-C), and low-density lipoprotein-cholesterol (LDL-C). Results: Phytochemical screening indicated the presence of flavonoids and saponins. The antioxidant activity of HB cleanser® bitters was dose dependent as it significantly (p<0.05) increased with increase in concentration when compared with ascorbic acid. HB bitters®at 1000 µg/ml significantly (p<0.05) inhibited lipid peroxidation (78.21±0.53 %) compared to ascorbic acid (94.43±0.53 %) in-vitro. The bitters at 1.29 ml/kg exhibited a non-statistically significant (P>0.05) decrease of total cholesterol and total triglyceride (2.32±0.15 mmol/L, 0.92±0.13 mmol /L) with a marked increase in low density lipoprotein-cholesterol (1.32±0.20 mmol/L) compared to control. Conclusion: The findings of this study have revealed that HB cleanser®bitters possesses good antioxidant activity and may increase low- density lipoprotein-cholesterol, therefore it should be used with caution. Peer Review History: Received: 5 August 2022; Revised: 9 September; Accepted: 17 October; Available online: 15 November 2022 Academic Editor: Dr. Gehan Fawzy Abdel Raoof Kandeel , Pharmacognosy Department, National Research Centre, Dokki, 12622, Giza, Egypt, gehankandeel9@yahoo.com Reviewers: Dr. Rima Benatoui,Laboratory of Applied Neuroendocrinology, Department of Biology, Faculty of Science, Badji Mokhtar University Annaba, Algeria. benattouiryma@gmail.com Dr. DANIYAN Oluwatoyin Michael, Obafemi Awolowo University, ILE-IFE, Nigeria, toyinpharm@gmail.com